The Cyberspace as a Common Heritage of Mankind: Governing Jurisdictional Limitations of the Internet By Virtue of International Law - Al Asyari, Haekal (2020)
It has been almost three decades since the first invention of the internet, which also gave birth to a novel common space area for mankind known as the Cyberspace. This unique environment consisting of global web of linked networks and computers transcends the traditional concept of jurisdiction and sovereignty inviting multi-disciplinary approach and an inclusive policy making strategy. The international architecture of the cyberspace shares a connection with the real world, with geographical servers and governments as well as the material effects of the development of international law, inherently creating the nature of Cyberspace regulation to also be international. Historically, the governance of common space areas such as the sea-bed, Antarctica and the outer space had an immediate and obvious rule applicable to its international situation. This has not been the case for Cyberspace where due to its unique characteristics, a majority consensus to agree on a unified international law governing it is difficult to reach. Thus, this research has reflected on the phenomena of the aforementioned common space areas, where an accepted regime has been adopted known as the Common Heritage of Mankind (CHM). The CHM has both its theoretical and practical stance in the sphere of international law serving as a fundamental legal basis for the governance of Cyberspace. This thesis has gathered a retrospective and normative approach to analyse the CHM’s conception into the sea, Antarctica, and outer space and drawing a hypothesis of the similarities that it has with the Cyberspace. First, due to the unstoppable development of technology, information, and communication, it is the burden for the law to adapt to this human evolution which drives the necessity for the Cyberspace to be governed under a uniform international law. As an area beyond national jurisdiction, the CHM acts as a general principle of law to govern the jurisdictional limitations. The Cyberspace possess a similar philosophical foundation to the Sea bed in ...